Prinsip-Prinsip Akuntansi Syariah dalam Laporan Keuangan Bank Syariah - Safira Armah; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the application of sharia accounting principles in the financial statements of Islamic banks in Indonesia, focusing on the implementation of Sharia Financial Accounting Standards (SAK Syariah) and its impact on the transparency of financial statements. The Islamic banking industry in Indonesia has experienced rapid development, but the application of sharia accounting in financial statements still faces a number of challenges, such as differences in interpretation of sharia provisions, limited human resources, and difficulties in adapting accounting standards to the ever-evolving economic conditions. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews and documentation studies of the financial statements of leading Islamic banks. The results of the study indicate that although most Islamic banks in Indonesia have implemented sharia accounting principles in accordance with the SAK Syariah guidelines, there are still differences in their application, especially in more complex transactions. The main challenges faced are differences in interpretation of sharia provisions and the limited number of auditors and practitioners who are competent in the field of sharia accounting. The application of sharia accounting principles contributes to increasing the transparency of financial statements, although there are still obstacles in terms of the general public's understanding of the technical terms used. This study also found that although most banks have followed the SAK Syariah guidelines, there are gaps in the application of sharia principles to more innovative financial products. Therefore, it is necessary to update the SAK Syariah to accommodate the development of more complex financial products and instruments, in order to improve the consistency and credibility of the financial statements of Islamic banks in Indonesia.